2023
DOI: 10.3390/life13081671
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Anti-Psoriasis Activity of Ficus carica Fruit Extracts via JAK-STAT Modulation

Jeong Hwa Lee,
Mi-Young Lee

Abstract: Psoriasis, a chronic and autoimmune inflammatory disorder of the skin, has been often underdiagnosed and underestimated despite its prevalence and considerable negative effects on the quality of life. In this study, the anti-inflammatory activity of Ficus carica fruit extract (FFE) was investigated against LPS-stimulated RAW 264.7 cells. The in vitro results showed that FFE reduced the production of nitric oxide (NO) and iNOS expression. Moreover, FFE reduced the level of β-hexosaminidase released with histami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results showed that the extract reduced nitric oxide production, and iNOS and COX-2 expression in inflammatory-activated cells significantly influenced the JAK-STAT signaling pathway associated with psoriasis and reduced the release of β-hexosaminidase. In mice, extract treatment decreased skin thickness and PASI score, and decreased epidermal dermis thickness, in addition to reducing STAT3 phosphorylation, all of which demonstrate that FC fruit extract may be a potential therapeutic agent for psoriasis [100].…”
Section: Ficus Carica In Psoriazismentioning
confidence: 80%
“…The results showed that the extract reduced nitric oxide production, and iNOS and COX-2 expression in inflammatory-activated cells significantly influenced the JAK-STAT signaling pathway associated with psoriasis and reduced the release of β-hexosaminidase. In mice, extract treatment decreased skin thickness and PASI score, and decreased epidermal dermis thickness, in addition to reducing STAT3 phosphorylation, all of which demonstrate that FC fruit extract may be a potential therapeutic agent for psoriasis [100].…”
Section: Ficus Carica In Psoriazismentioning
confidence: 80%
“…Here in the survey, mice treated with S. deserti methanolic extract harboured lower levels of cytokines compared to the control group. Similarly, Ficus carica [29], and Dysidea avara [30] extracts showed high anti-psoriasis effects through the reduction in rates of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 98%